Manajemen Laba dalam Persepsi Etis Akuntan di Jawa Timur - Lontoh, Frederich Oscar; Lindrawati, . (Jurnal Widya Manajemen & Akuntansi, 2004)
The result of this research shows that the perception among accountants of all groups considering the earnings management ct don't have any significant difference. Only two of that s*factor was had any influence to the perception of the accountants considering the manajemen laba act. Consistency to GAAP and materiality is the only factors that shows some significant influence.